Whole-Genome Sequence of the C57L/J Mouse Inbred Strain - Ananda, Guruprasad (Genetics Society of America, 2014)
We sequenced the complete genome of the widely used C57L/J mouse inbred strain. With 40× average coverage, we compared the C57L/J sequence with that of the C57BL/6J and identified many known as well as novel private variants. This genome sequence adds another strain to the growing number of mouse inbred strains with complete genome sequences and is a valuable resource to the scientific community.